Controlling corruption in India: Various approaches and their efficacy - Chowdhry, Javid (2011)
A sufficient number of oversight institutions have been constitutionally established in India. The institutions like Comptroller and Auditor General, Election Commission and Central Vigilance Commission are adequately empowered. The heads of thes institutions have an assured tenure and their functioning is independent of the executive. Yet the widespread perception is gaining credence that all the institutions put together have not suceeded in curbing corruption in the public domain to a significant extent. This article briefly discusses the functioning of these institutions and analyses why these institutions have not been as effective as was expected of them. - Reproduced.
Keywords: Corruption - India; Corruption